Small Molecule Inhibitors of CRM1 - Ferreira, Bibiana I.; Cautain, Bastien; Grenho, Inês; Link, Wolfgang (Frontiers in Pharmacology, 2020)
Cancer cells utilize the processes of nuclear-cytoplasmic transport through the nuclear pore complex of a cell to effectively evade anti-neoplastic mechanisms. Several tumor-suppressive proteins have been shown to be excluded from the cell nucleus in cancer cells by the nuclear export receptor CRM1 and abnormal expression of CRM1 is oncogenic. Inhibition of CRM-1 has long been postulated as an attractive therapeutic option for the treatment of cancer and to overcome therapy resistance. However the first nuclear export inhibitors failed or never entered into clinical trials. More recently CRM1 reemerged as a cancer target and a successful proof of concept was achieved with the clinical approval of Selinexor. As the pathway regulating CRM1 is governed by protein-protein interactions (PPIs) which are considered to be challenging to target with small molecules, the chemical complexity of natural products is a promising perspective for the discovery of novel nuclear export inhibitors. Several screening campaigns have been performed and several natural product-based nuclear export inhibitors have been identified. In this review we provide an overview over the role of CRM1-mediated nuclear export in cancer and the effort made to identify and develop nuclear export inhibitors in particular from natural sources.